1983
DOI: 10.1038/clpt.1983.102
|View full text |Cite
|
Sign up to set email alerts
|

Isosorbide dinitrate kinetics and dynamics after intravenous, sublingual, and percutaneous dosing in angina

Abstract: Isosorbide dinitrate (ISDN) kinetics and dynamics were examined after various routes of administration for angina. Given intravenously, ISDN kinetics were apparently linear over the range of infusion rate (0.083 and 0.133 mg/min) and duration (15 min and 1 and 2 hr) studied. Mean +/- SD systemic clearance of ISDN was 3.4 +/- 1.4 l/min and volume of distribution (VdSS or Vdarea) about 100 l. These data are consistent with the presence of extensive extrahepatic metabolism. In six patients, sublingual ISDN (5 mg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…It was observed that the changes in standing systolic pressure were greater during the declining phase than in the ascending phase after IV and sublingual administration [44], this correlated with previous studies after oral administration [108]. …”
Section: Counter-clockwise Hysteresissupporting
confidence: 79%
See 1 more Smart Citation
“…It was observed that the changes in standing systolic pressure were greater during the declining phase than in the ascending phase after IV and sublingual administration [44], this correlated with previous studies after oral administration [108]. …”
Section: Counter-clockwise Hysteresissupporting
confidence: 79%
“…The organic nitrate isosorbide dinitrate (ISDN) exhibited counter-clockwise hysteresis after intravenous infusion (0.133 mg/min for 15 min) or sublingual (5 mg) administration (Figure 5) [44]. It was observed that the changes in standing systolic pressure were greater during the declining phase than in the ascending phase after IV and sublingual administration [44], this correlated with previous studies after oral administration [108].…”
Section: Counter-clockwise Hysteresissupporting
confidence: 67%
“…After a single sublingual isosorbide dinitrate dose a counterclockwise hysteresis of the plasma concentration-effect relationship exists; i.e., a greater effect is observed at the same plasma isosorbide dinitrate concentration (Morrison et al 1983) which influences data interpretation. The metabolites may also reduce denitration of isosorbide dinitrate in the vessel wall (Fung 1985).…”
Section: Pharmacokineticsmentioning
confidence: 98%
“…The mean elimination half-life of isosorbide dinitrate is approximately 1 hour, but may vary from 35 to 120 minutes. However, after long term dosing, a much longer terminal phase tl;' of 7.7 ± 2.6 hours was reported, as a result of accumulation of metabolite isosorbide-5-mononitrate, which reduces hepatic isosorbide dinitrate extraction (Morrison et al 1983).…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation